Manifestations of hysteria in Nawal El Saadawi's Woman at Point Zero - Abdullah, Omar Mohammed; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur; Mani, Manimangai (Penerbit Universiti Kebangsaan Malaysia, 2015)
A well-known Middle Eastern author, Nawal El Saadawi shouldered the grave responsibility of defending the rights of women in her country and the Middle East in general. Hysteria is one of the main problems inhabiting the female characters of El Saadawi’s fiction. Many of those female characters suffer hysteric symptoms which manifest as a consequence of sexual violations such as rape, molestation and female circumcision in patriarchal-centered communities. These violations lead to psychological traumas which can eventually give rise to hysteria. Symptoms of alienation, loss of speech, fear, anorexia, disturbed sleep and many others are classified under the bold title of hysteria. Freud attributes the emergence of hysteria to sexual experiences that a subject goes through in childhood, which appear later in the guise of the aforementioned symptoms. This paper will focus on Hysteria according to Freudian perspectives, in order to explore its symptoms and reaction, as well as action undertaken to absolve and actualize the self in El Saadawi’s Woman at Point Zero. It also underscores how characters go through this process to gain their subjectivity in this novel.